2019
DOI: 10.9734/jeai/2019/v34i330177
|View full text |Cite
|
Sign up to set email alerts
|

Soil Nitrogen Contents as Affected by Composts Enriched with Organic Nitrogen Sources

Abstract: Information is scanty on the potentials of agricultural wastes to enrich composts whose low nitrogen (N) content limits their use in organic farming. This study involved enriching composts - cow dung + sawdust (CDSD) and poultry droppings + sawdust (PDSD) with N from bone, blood, hoof and horn meals; and neem leaf and tithonia leaf meals and their incubation in the soil for 16 weeks. Cow dung and sawdust (CDSD), poultry manure and sawdust (PMSD) in 1:1 ratios were composted in separate heaps and samples taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…On the other hands, the available poultry houses and pens are continuous sources of poultry dung which are routinely burnt and thereby causing air pollution, whereas these poultry droppings had been evaluated to be the most valuable of all manures produced by livestock (Charles and Donald, 2012). Fawole et al (2019 and confirmed the beneficial effects of organic sources, including poultry droppings on the nitrogen and phosphorus contents of soils, respectively. Likewise, Omolayo et al, (2011) recommended application of 30 MT/ha of broiler droppings for optimum and sustainable production of vegetables, as it was observed that application of poultry manure, particularly broilers at 30 MT/ha improved vegetative growth and yield of Amaranthus.…”
Section: Justification Of the Studymentioning
confidence: 58%
“…On the other hands, the available poultry houses and pens are continuous sources of poultry dung which are routinely burnt and thereby causing air pollution, whereas these poultry droppings had been evaluated to be the most valuable of all manures produced by livestock (Charles and Donald, 2012). Fawole et al (2019 and confirmed the beneficial effects of organic sources, including poultry droppings on the nitrogen and phosphorus contents of soils, respectively. Likewise, Omolayo et al, (2011) recommended application of 30 MT/ha of broiler droppings for optimum and sustainable production of vegetables, as it was observed that application of poultry manure, particularly broilers at 30 MT/ha improved vegetative growth and yield of Amaranthus.…”
Section: Justification Of the Studymentioning
confidence: 58%
“…The quick releasing ability of NPK 19 was evident in its ability to produce the longest vines in the earlier days of this study, though not significantly different from the enriched compost at 30 and 40 t/ha; an indication that appropriately N-enriched composts would compete effectively with the quick-releasing NPK 15 . In an incubation study to monitor the quantities of N released from soils treated with composts enriched with organic nitrogen sources, it was observed that cattle dung/sawdust compost enriched with neem leaf meal (CDSNM) is an early and steady releaser of N 12 . The NPK did not produce any significantly better growth parameter than the CDSNM applied at 40 t/ha in this study even in the earlier days of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…This invariably confirms the earlier submission that the N contents of some organically N-enriched composts at 4 and 8 weeks of incubation were enough to make the enriched composts suitable for the production of short-season crops such as leaf vegetables (leaf amaranth, Corchorus olitorius, Celosia argentea, Talinum fruticosum etc.) while some with high N contents at 12 and 16 weeks of incubation will support the growth needed for optimum yield of long-duration leaf and fruit vegetables such as okra, tomato, sweet corn, eggplant, egusi (Citrullus lanatus), worowo (Senecio biafrae), fluted pumpkin (Telfairia occidentalis) 12 . This confirmation therefore establishes the fact that CDSNM would conveniently replace NPK in the domestication and improved production of worowo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cattle abattoir wastes and leaves can be dried, ground into powder (meals) and used as materials to supplement the N content of composts (Fawole et al, 2019;Rhoades, 2020). All the nutrients taken up by the plants and animals which generate the wastes are contained in manures but the quality is often measured by the N contents whose eventual release through mineralization processes would provide the explanation for crop responses to manure application.…”
Section: Introductionmentioning
confidence: 99%